Understanding the Profile and Needs of Abused Men: Exploring Call Data From a Male Domestic Violence Charity in the United Kingdom - Hine, Benjamin (Journal of interpersonal violence, 2022)
Current understandings on service engagement by male victims of domestic violence and abuse (DVA) within the United Kingdom (UK) have generally been captured by qualitative research. As such, large-scale quantitative data detailing the profile, needs and outcomes of abused men, upon both presentation and use of services, is currently lacking. The present study analyzed the client data of 719 callers to a domestic abuse helpline for men in the UK. Findings showed that the overwhelming majority of callers reported they were abused by female perpetrators, most of whom were still their current partner, and that many of the men were fathers. Vulnerable populations (GBTQ+ and disabled men) were under-represented in the sample. Most men were seeking emotional support, along with a range of practical advice and signposting to other services. The confidentiality of the helpline was crucial for many men, and almost half had struggled to access the service (suggesting a severe lack of resourcing). Findings are discussed in relation to the need for gender-inclusive services, which cater for the unique challenges and barriers experienced by abused men.